Preparation Of Village Government Personnel Implement Village Autonomy - Jehan Fuliza Ahmad; Sri Kusriyah (Law Development Journal, 2020)
This research raises problems regarding the readiness of village government officials in implementing village autonomy, to find out what obstacles they face in its implementation and solutions in dealing with problems faced. This study used a sociological juridical research method with descriptive research specifications. This research was conducted by direct research in Galih Village. With data sources derived from primary data and secondary data, and data analysis used is descriptive qualitative data collection techniques by means of interviews and document study. This study conducted interviews at the Galih Village Hall Office. From this research, it was found that the village government apparatus of Galih played a role as maker and implementer of autonomy in Galih Village, including making work programs that were taken from the aspirations of the village community. In implementing autonomy in the village, the problems of human resources and operational funds are obstacles experienced by the Galih Village government apparatus, with these problems the Galih Village government apparatus conducts training to add insight to village officials and manage village finances for unexpected events. From this research it can be concluded that the implementation of autonomy in Galih Village has been running according to Act No. 6 of 2014.